Film-like chitin/polyethylenimine biosorbent for highly efficient removal of uranyl-carbonate compounds from water. Issue 4 (August 2021) - Lin, Ziming; Chen, Lifeng; Ye, Zhenxiong; Chen, Xiyong; Wang, Xinpeng; Wei, Yuezhou
Abstract: Uranium contamination in groundwater has been increasingly reported, while biosorbents for the decontamination attracts growing attention because of their distinct advantages of abundant raw materials and eco-friendliness. Herein, a film-like chitin/polyethylenimine biosorbent (CH-PEI) was prepared and employed in the removal of uranyl-carbonate compounds from water. Fourier transform infrared spectra, element analysis, scanning electron microscopy/energy dispersive X-ray spectroscopy, N2 adsorption-desorption isotherms and X-ray photoelectron spectroscopy were used to characterize the biosorbent. Besides, thermodynamic calculation and various batch experiments were conducted to investigate the adsorption performances of CH-PEI for uranyl removal from carbonate solution. The results showed that the biosorbent possessed a unique hierarchically porous structure and a high nitrogen content. The batch experiments exhibited that it obtained the maximum adsorption capacity at pH = 6. Notably, CH-PEI could reach sorption equilibrium within 4 h at the initial concentration of 50 mg/L. The maximum adsorption capacity were 247.04 mg/g and 1023.74 mg/g at the initial concentrations of 50 mg/L and 300 mg/L. The kinetics and isotherm data were well fitted by pseudo-second-order and Langmuir models. It could remove 98.9% of uranium in the simulated groundwater. The biosorbent showed fast regeneration, good structural stability and reusability in 5 cycles. Furthermore, the adsorption mechanism was confirmed to be anion exchange and electrostatic attraction between nitrogen species and uranyl-carbonate complexes through FT-IR and XPS analysis. Considering its low costs, high efficiency and easy collection, CH-PEI would be a promising biosorbent for uranium removal from groundwater. This study provides a potential technique for uranium removal using chitin-based adsorbents. Graphical Abstract: ga1 Highlights: A film-like chitin/polyethylenimine biosorbent was synthesized and characterized. The prepared material possessed a high nitrogen content and a hierarchical porous structure. The developed material showed the comparable uranium adsorption capacity (950.49 mg/g) to other biosorbents. The sorbent exhibited a fast regeneration and maintained its integrity and structure after 5 cycles. The adsorption mechanisms were proposed to be anion exchange and electrostatic attraction between the nitrogen species and uranyl-carbonate compounds.